2013
DOI: 10.1024/0300-9831/a000146
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Determination of Coenzyme Q10 in Food Supplements Using 1H NMR Spectroscopy

Abstract: A methodology utilizing 1H NMR spectroscopy has been developed to measure the concentration of coenzyme Q10 (CoQ10) in dietary supplements. For sample preparation, a very simple dilution with deuterated chloroform and addition of internal standard is sufficient. CoQ10 produces a distinct peak of the CH groups in the isoprene side chain of the molecule in the δ 5.15 - 5.05 ppm range, where it can be distinguished from other matrix compounds. The method was shown to be of adequate sensitivity with a limit of det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Each found that some products on the market contained substantially less CoQ 10 than was listed on the label. 7,8 Substandard and counterfeit drug products are a worldwide problem. 9 The same is probably true for nutritional supplements.…”
Section: Perspec Tivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Each found that some products on the market contained substantially less CoQ 10 than was listed on the label. 7,8 Substandard and counterfeit drug products are a worldwide problem. 9 The same is probably true for nutritional supplements.…”
Section: Perspec Tivesmentioning
confidence: 99%
“…Two papers presenting analytical methods for CoQ 10 presented data on content of supplement products. Each found that some products on the market contained substantially less CoQ 10 than was listed on the label 7 , 8 . Substandard and counterfeit drug products are a worldwide problem 9 .…”
mentioning
confidence: 99%
“…However, for routine analysis in food and drug testing laboratories, alternative analytical methods (such as spectroscopic screening techniques) are desirable. As a state control laboratory, we have already developed fast and accurate methods for targeted determination of active compounds in several matrices including dietary supplements and alcoholic beverages using nuclear magnetic resonance (NMR) spectroscopy . This work presents for the first time an NMR‐based method with minimal sample preparation for determination of DMAA in sports nutrition and dietary supplements.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most promising analytical methods for the screening and the evaluation of multi-component matrices, such as dietary supplements, is Nuclear Magnetic Resonance (NMR) spectroscopy 14,15 . NMR spectroscopy has several advantages: it is a non-destructive and quantitative technique, it requires minimal to no sample preparation, and it is characterized by excellent accuracy and reproducibility.…”
mentioning
confidence: 99%